Vascular contribution to hyperglycaemia-induced hemichorea. - Ahmad, A; Paliwal, P; Wakerley, B; Teoh, H; Sharma, V (2013)
Hemichorea, due to contralateral basal ganglia dysfunction, is well described in patients with hyperglycaemia but the underlying mechanism remains poorly understood. We present clinical and radiological data that support ipsilateral vascular compromise to the basal ganglia in such cases. We suggest vascular evaluation in patients with unilateral neurological phenomena secondary to suspected systemic or metabolic disorders.